Plasma-catalytic reforming of ethanol: influence of air activation rate and reforming temperature - Nedybaliuk, O.A.; Chernyak, V.Ya.; Fedirchyk, I.I.; Demchina, V.P.; Bortyshevsky, V.A.; Korzh, R.V. (Вопросы атомной науки и техники, 2016)
This paper presents the study of the influence that air activation rate and reforming temperature have on the
gaseous products composition and conversion efficiency during the plasma-catalytic reforming of ethanol. The
analysis of product composition showed that the conversion efficiency of ethanol has a maximum in the studied
range of reforming temperatures. Researched system provided high reforming efficiency and high hydrogen energy
yield at the lower temperatures than traditional conversion technologies. Изложено исследование влияния степени активации воздуха и температуры реформирования на состав
газообразных продуктов плазменно-каталитического реформирования этанола и на его эффективность.
Анализ состава полученных продуктов показал, что эффективность реформирования имеет максимум в
исследованном диапазоне температур. Исследованная система имеет высокую эффективность
реформирования и высокий энергетический выход водорода при температурах ниже, чем в традиционных
технологиях реформирования. Представлено дослідження впливу ступеня активації повітря та температури реформування на склад
газоподібних продуктів реформування етанолу та на його ефективність. Аналіз складу продуктів
реформування показав, що ефективність реформування має максимум у дослідженому діапазоні температур
реформування. Досліджена система забезпечує високу ефективність реформування та високий енергетичний
вихід водню за температур, що є нижчими, ніж у традиційних технологіях реформування.